The Correlation Between Aldosterone and Leukocyte-Related Inflammation: A Comparison Between Patients with Primary Aldosteronism and Essential Hypertension - Rao KR; Bao RY; Ming H; Liu JW; Dong YF (Dove Medical Press, 2023)
Kun-Rui Rao,1,* Ru-Yi Bao,1,* Hu Ming,1 Jian-Wei Liu,1 Yi-Fei Dong1,2 1Department of Cardiovascular Medicine, The Second Affiliated Hospital of Nanchang University, Nanchang, People's Republic of China; 2Key Laboratory of Molecular Biology in Jiangxi Province, Nanchang, People's Republic of China*These authors contributed equally to this workCorrespondence: Yi-Fei Dong, Department of Cardiovascular Medicine, the Second Affiliated Hospital of Nanchang University, Nanchang, People's Republic of China, Email yf_dong66@126.comBackground: Hypertension patients with primary aldosteronism (PA) have a higher risk of cardiovascular complications than blood pressure-matched essential hypertension (EH) patients. The cause may be closely related to inflammation. We explored the correlations between leukocyte-related inflammation parameters and plasma aldosterone concentration (PAC) in PA patients and clinical characteristics-matched EH patients.Methods: A total of 346 PA and 346 sex, age and 24-h blood pressure-matched EH patients at the 2nd Affiliated Hospital of Nanchang University from January 2020 to June 2021 were enrolled in this study. The differences and correlations of aldosterone and leukocyte parameters between the two groups were analyzed.Results: Compared with EH patients, the lymphocyte count was significantly lower (P = 0.004), the neutrophil-lymphocyte ratio (NLR) (P = 0.023) and the monocyte-lymphocyte ratio (MLR) (P = 0.037) were significantly higher in PA patients. Linear regression analysis and multivariate regression analysis identified that lymphocyte count, NLR and MLR were significantly and independently correlated with PAC in PA patients, and the correlations were stronger with increasing levels of aldosterone. However, in EH patients, only NLR maintained an independent correlation with PAC.Conclusion: Leukocyte-related inflammation parameters, including lymphocyte count, NLR, and MLR, were significantly and independently correlated with PAC in PA patients. The correlations were stronger with increasing levels of aldosterone. However, the above correlations were not always present in patients with EH matched for clinical characteristics.Keywords: aldosterone, inflammation, leukocytes, primary aldosteronism, essential hypertension